Research progress of symptom clusters in maintenance hemodialysis patients - Zhao Jie; Liu Xiao-hui; Pang Xin-xin; Dai Nan; Nie Ya-jie; Zhang Xiao-fei (Linchuang shenzangbing zazhi)
The global number of patients with end-stage renal disease is on the rise. Maintenance hemodialysis， as the most widely used renal replacement therapy， can prolong the life of patients However， treatment-related various complications interact with each other to form a symptom cluster， which seriously affects the prognosis and the quality of life of patients. In this paper， the name and manifestation， risk factors， assessment tools and intervention measures of symptom clusters in maintenance hemodialysis patients were reviewed， and the future research direction was prospected.